Forest condition in the Congo Basin for the assessment of ecosystem conservation status - Aurélie C. Shapiro (Elsevier, 2021)
Quantifying ecological condition, notably the extent of forest degradation is important for understanding and designing measures to protect biodiversity and enhancing the capacity of forests to deliver ecosystem services. Conservation planning, particularly the prioritization of management interventions for forests, is often lacking spatial data on forest degradation, and it is often overlooked within decision-making processes. We develop a continuous metric termed Forest Condition (FC) which aims to measure the degree of forest degradation on a scale from 0 to 100, incorporating the temporal history of forest change over any spatial extent. We parameterize this metric based on estimated changes in above ground biomass in the context of forest fragmentation over time to estimate a continuous measure of forest degradation for Congo Basin countries. We estimate that just <70% of Congo Basin forests remain fully intact, a decrease from 78% in the year 2000. FC was validated by direct remote sensing measurements from Landsat imagery for DRC. Results showed that FC was significantly positively correlated with forest canopy cover, gap area per hectare, and magnitude of temporal change in Normalized Burn Ratio. We tested the ability of FC to distinguish primary and secondary degradation and deforestation and found significant differences in gap area and spectral anomalies to validate our theoretical model. We apply the IUCN Red List of Ecosystems criteria to demonstrate the integration of forest condition to assess the risk of ecosystem collapse. Based on this assessment, we found that without including FC in the assessment of biotic disruption, 12 ecosystems representing over 11% of forested area in 2015 would not have been assigned a threat status, and an additional 9 ecosystems would have a lower threat status. Our overall assessment of ecosystems found about half of all Congo Basin ecosystem types, accounting for 20% of all forest area are threatened to some degree, including 4 ecosystems (<1% of total area) which are critically engendered. FC is a transferrable and scalable assessment to support forest monitoring, planning, and management.